2010
DOI: 10.1021/jm100212x
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Amide Nitrones: A New Class of Protective Agents Acting as Modifiers of Mitochondrial Metabolism

Abstract: Our group has demonstrated that the amphiphilic character of alpha-phenyl-N-tert-butyl nitrone based agents is a key feature in determining their bioactivity and protection against oxidative toxicity. In this work, we report the synthesis of a new class of amphiphilic amide nitrones. Their hydroxyl radical scavenging activity and radical reducing potency were shown using ABTS competition and ABTS(+) reduction assays, respectively. Cyclic voltammetry was used to investigate their redox behavior, and the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 73 publications
3
29
0
Order By: Relevance
“…DMPO has been widely employed as spin trapping agents with more superior properties than that of PBN-based nitrones in terms of reactivity to O 2 •− and HO 2 • [76]. Therefore, attempts had been made to conjugate cyclic nitrones to several target specific groups in order to facilitate their delivery to specific subcellular compartments [34, 7880] since the poor target specificity of some of the natural antioxidants such as vitamin E, vitamin C, or lipoic acid are limiting their applications against ROS-induced CVDs [19, 81, 82]. …”
Section: Discussionmentioning
confidence: 99%
“…DMPO has been widely employed as spin trapping agents with more superior properties than that of PBN-based nitrones in terms of reactivity to O 2 •− and HO 2 • [76]. Therefore, attempts had been made to conjugate cyclic nitrones to several target specific groups in order to facilitate their delivery to specific subcellular compartments [34, 7880] since the poor target specificity of some of the natural antioxidants such as vitamin E, vitamin C, or lipoic acid are limiting their applications against ROS-induced CVDs [19, 81, 82]. …”
Section: Discussionmentioning
confidence: 99%
“…First, 2-methyl-2-nitro-1-propanol was activated using 1,1′-carbonyldiimidazole (CDI) in the presence of 4-dimethylaminopyridine (DMAP) in THF, and then methylamine was added to the reaction mixture to give compound 3 after purification in 98% yield. In parallel, 2-methyl-2-nitropropanamine ( 4 ) was obtained from 2-methyl-2-nitro-1-propanol in three steps 9 and was then acetylated to give the nitro compound 5 in 94% yield. The one-pot reduction/condensation of compounds 3 and 5 to benzaldehyde after purification by flash chromatography and two successive crystallization from EtOAc/ n -hexane led to nitrones 6 (also called PBN-CH 2 OCONHMe) and 7 (also called PBN-CH 2 NHAc) in 70% and 68% yields, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…79 Selective targeting is usually achieved by conjugating the nitronyl group to specific target ligands, and therefore, the choice of linker groups for optimal spin trapping properties is highly desirable. In addition to the types of ligands that are tethered to nitrones, it has been demonstrated that the nature of the linker group also affects its bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…New amphiphilic noncyclic nitrones, bearing a polar lactobionic acid moiety and an alkyl lipophilic chain, have been developed by Durand et al Compound 26 (Table ) effectively decreased electron and proton leak and hydrogen peroxide formation in isolated rat brain mitochondria, without affecting the mitochondrial membrane potential. Due to its ability to accumulate in mitochondria, it can act as a radical scavenger in situ and prevent ROS/RNS‐induced mitochondrial dysfunction.…”
Section: Spin Trapsmentioning
confidence: 99%